2021
DOI: 10.1111/jora.12688
|View full text |Cite
|
Sign up to set email alerts
|

Bullying Prevention in Adolescence: Solutions and New Challenges from the Past Decade

Abstract: Bullying among youth at school continues to be a global challenge. Being exposed to bullying may be especially hurtful in adolescence, a vulnerable period during which both peer group belonging and status become key concerns. In the current review, we first summarize the effectiveness of the solutions that were offered a decade ago in the form of anti-bullying programs. We proceed by highlighting some intriguing challenges concomitant to, or emerging from these solutions, focusing especially on their relevance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
56
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(63 citation statements)
references
References 244 publications
1
56
0
6
Order By: Relevance
“…Knowing which strategy will be most effective when intervening in cases of bullying is important for teachers, especially when the case involves adolescent perpetrators. Indeed, tackling school bullying has been found to be more challenging with adolescents than with children (Yeager et al, 2015 ), possibly because of decreased obedience to adult authority and a stronger desire for status among peers in this developmental period (see Salmivalli et al, 2021 ). Previous research on this topic indicates that condemning the bullying behavior and trying to raise empathy for the victim are both effective strategies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Knowing which strategy will be most effective when intervening in cases of bullying is important for teachers, especially when the case involves adolescent perpetrators. Indeed, tackling school bullying has been found to be more challenging with adolescents than with children (Yeager et al, 2015 ), possibly because of decreased obedience to adult authority and a stronger desire for status among peers in this developmental period (see Salmivalli et al, 2021 ). Previous research on this topic indicates that condemning the bullying behavior and trying to raise empathy for the victim are both effective strategies.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, this study examines whether students’ responses to the different messages vary as a function of their levels of empathy and callous-unemotional traits, which have been shown to be related to bullying behavior (Geel et al, 2017 ; Mitsopoulou & Giovazolias, 2015 ). As anti-bullying interventions tend to become less effective in adolescence (e.g., Salmivalli et al, 2021 ; Yeager et al, 2015 ), it is important to understand students’ responsiveness to various intervention strategies at this age. For this reason, the present experiment was conducted with early adolescents in their first year of secondary school.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, high-status victims self-reported more concurrent and prospective bullying and were seen by peers as more proactively and indirectly aggressive concurrently. The positive association between status and aggressive behavior is well-established (e.g., Salmivalli et al, 2021 ). The current study examined whether the victimization experience of those youth at the top of the social hierarchy would amplify this association.…”
Section: Discussionmentioning
confidence: 97%
“…To create clear comparisons, the current study focused on victims and non-victims who were either low or high in popularity, resulting in four groups: high-status victims, lower-status victims, high-status non-victims, and lower-status non-victims. The current study focused on aggression and alcohol use, which are both positively associated with popularity (Mayeux et al, 2008 ; Salmivalli et al, 2021 ), but are also two common responses to peer victimization (for aggression, see, e.g., Malamut & Salmivalli, 2021 ; for alcohol use, see, e.g., Manglio et al, 2017 ). Given that both victimization and popularity can be risk factors for these behaviors, the current study directly examined whether they jointly conferred risk for aggression and alcohol use compared to popularity or victimization alone.…”
Section: Introductionmentioning
confidence: 99%
“…However, bullying affects students worldwide and has been shown to have potentially serious and long-lasting effects on health, well-being, academic performance, and occupational success (Burger & Bachmann, 2021 ), not only for victims but for all students involved (Hysing et al, 2021 ). This is particularly true for students in early adolescence where bullying peaks (Swearer et al, 2017 ) and where students are even at a higher risk for developing mental health disorders due to changes in social dynamics, biology, and cognition (Salmivalli et al, 2021 ). It has been demonstrated that teachers can stop bullying (Troop-Gordon & Ladd, 2015 ) and that teacher interventions have a central role in the fight against bullying (Colpin et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%